Multipurpose leguminous trees and shrubs for agroforestry - Nair, P. K.R.; Fernandes, E. C.M.; Wanbugu, P. N. (Pesquisa Agropecuaria Brasileira, 2014)
An overview of the various agroforestry systems and practices that exist around the tropics and subtropics indicates that there are various ways in which farmers deliberately incorporate trees and shrubs on farm production fields. Many of the species so incorporated are legumes. The role of woody perennials in agroforestry systems can be productive and/or protective. The former includes the production of food, fodder, fuelwood, mulch, green manure, wood and various other useful products. The most important protective functions entail the use of woody perennials for soil protection and conservation, and for enhancement of soil's productivity on a sustainable basis, especially on account of the nitrogen-fixing capacity of the vast majority of them. Legumes are not the only group of woody species that have potential role in agroforestry, but they offer by far the maximum range of choice of woody species for agroforestry in terms of their economic uses as well as ecological adaptability. In addition to the several leguminous woody species that are well known in agroforestry, there are many whose potentials have hitherto not been fully understood. An evaluation of the agroforestry potentials of a few leguminous species from the point of view of their growth characteristics, ecological adaptability, combining ability with other species and uses/ functions is presented. The science of agroforestry is still in its infancy. There is yet nobody of knowledge on the various management aspects of these potentially promising group of plants based on systematic research. However, some trials have recently been initiated in several places around the world. ICRAF, in its capacity as an international research council with a global mandate to catalyze and promote research in agroforestry, has assembled several multipurpose leguminous trees and shrubs of agroforestry potential at the Council's recently-established Field Station in Machakos, Kenya, primarly for demonstration and training purposes.
Keywords: N2 fixation